Methane emission from the Western Siberia’s wetland ecosystems in 2000–2050 - Anatoly A. Lagutin; Nikolay V. Volkov; Egor Yu. Mordvin (Acta Biologica Sibirica, 2024)
The interannual variability of methane emissions from wetland ecosystems of Western Siberia in 2000–2050 has been investigated. Calculations of CH₄ emission were performed using the approach, in which the total daily methane flux is determined by the sum of positive temperatures accumulated in the soil at that time and its moisture content. Required characteristics of the soil were obtained using regional climate model RegCM4. The reanalysis NCEP-DOE AMIP-II (R2) and data of HadGEM2-ES global model for the RCP4.5 and RCP8.5 evolution scenario of the global climate system were used to define the initial and boundary conditions. It was found that for Western Siberia’s wetland complexes, analyzed in this paper, the model estimates for methane emission in 2000–2013 vary from ~3.5 to ~5.5 Tg CH₄/yr. The average value of emission is 4.34 TgCH₄/yr. The rate of change of methane emission during this period is almost neutral. Growth of CH₄ emission is observed only in the areas of tundra and forest tundra. Forecast values of methane emission obtained for the period 2021–2050 for scenarios RCP4.5 and RCP8.5 ranges from 3.9 up to 7.6 Tg CH₄/yr. The average emission values are 5.0 and 5.8 Tg CH₄/yr, respectively. Trends of CH₄ emission for this period are also practically neutral.